2002
DOI: 10.1128/jb.184.4.1180-1186.2002
|View full text |Cite
|
Sign up to set email alerts
|

High Genetic Variability of the agr Locus in Staphylococcus Species

Abstract: The agr quorum-sensing and signal transduction system was initially described in Staphylococcus aureus, where four distinct allelic variants have been sequenced. Western blotting suggests the presence of homologous loci in many other staphylococci, and this has been confirmed for S. epidermidis and S. lugdunensis. In this study we isolated agr-like loci from a range of staphylococci by using PCR amplification from primers common to the six published agr sequences and bracketing the most variable region, associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
176
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 191 publications
(192 citation statements)
references
References 38 publications
12
176
2
2
Order By: Relevance
“…In our study, we found agr mutations and three agr groups of S. epidermidis. Similar to the findings of Dufour et al (2002), most pathogenic S. epidermidis isolates were in agr group I. Pathogenic S. epidermidis isolates comprised 68 . 2 % group I, 19 .…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…In our study, we found agr mutations and three agr groups of S. epidermidis. Similar to the findings of Dufour et al (2002), most pathogenic S. epidermidis isolates were in agr group I. Pathogenic S. epidermidis isolates comprised 68 . 2 % group I, 19 .…”
Section: Resultssupporting
confidence: 76%
“…The agr locus in staphylococci has been shown to be polymorphic (Moore & Lindsay, 2001;Dufour et al, 2002; Jarraud et al, 2000Jarraud et al, , 2002. The agr locus in S. aureus can be divided into four distinct genetic groups.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these assays, e.g. amplification of the thermonuclease (nuc) gene (Chesneau et al, 1993), the Sa826 bp fragment (Štěpán et al, 2001), the coagulase (coa) gene (Schmitz et al, 1997), the femA regulator gene (Vannuffel et al, 1995) and the accessory gene regulator (agr Sa ) locus (Dufour et al, 2002), gave negative results.The DNA-DNA hybridization experiments and analysis of the DNA G+C content were performed as described by Mannerová et al (2003). On the basis of the results obtained, the novel strains could not be assigned to any of the known staphylococcal species and therefore a polyphasic taxonomic approach was used for their analysis.…”
mentioning
confidence: 99%